Probiotics in critical illness - Is there a role in intensive care? - Hema Kumar; Rakshay Shetty (Wolters Kluwer Medknow Publications, 2015)
Probiotics are living microbes, when adequately ingested confer benefits to the host which include shortened duration of infection or decreased susceptibility to pathogens. Probiotics improve gut banier function, restore non-pathogenic digestive flora, prevent colonization by pathogenic bacteria and have role in immunomodulation. In the era of increasing antibacterial resistance and fewer new antibiotics in the research pipeline, non-antibiotic approaches like use of probiotics offer a ray of hope to clinician in the prevention of nosocomial infections in critical ill patients. Till to date, trials conducted on the role of probiotics in critically ill patients have shown significant heterogenicity in clinical outcomes, type of strain studied, dose and duration of therapy. Hence, the current data does not offer sufficient evidence to draw a conclusion regarding clinical indications of probiotics in critically ill. Well designed clinical trials are needed to validate the effects of particular probiotics given at specific dosages and for specific treatment durations. Although probiotics are generally safe in critically ill, more information is needed on safety profile of probiotics particularly in immunocompromised patients.